Do socio-cultural factors influence medical students' health status and health-promoting behaviors? A cross-sectional multicenter study in Germany and Hungary - Henna Riemenschneider; Péter Balázs; Erika Balogh; Axel Bartels; Antje Bergmann; Károly Cseh; Nora Faubl; Zsuzsanna Füzesi; Ferenc Horváth; István Kiss; Jörg Schelling; András Terebessy; et al. (BMC, 2016)
Abstract Background Physical and mental health is important for coping with the high requirements of medical studies that are associated with a higher risk for severe stress, insomnia, smoking, harmful alcohol consumption and easier access to drugs. Health behaviors of medical students influence not just their own health but also the health of their future patients. We examined whether socio-cultural factors can explain differences in students' health status and health-promoting behaviors. Methods A multicenter cross-sectional survey in Germany (Dresden, Munich) and Hungary (Budapest, Pécs) enclosed international medical students in their 1st, 3rd and 5th academic years. The students were invited to voluntarily and anonymously complete a questionnaire on different aspects of health behavior during obligatory seminars and lectures in 2014. The response rate of the total sample was 56.2 % (n = 2935); the subgroup analysis enclosed data of German (n = 1289), Hungarian (n = 1057) and Norwegian (n = 148) students. Results A high number of Norwegian students (84.5 %) assessed their health status as very good/excellent. In comparison, only 60.3 % of the Hungarian and 70.7 % of the German participants reported a very good/excellent health status. The distributions were comparable between the study sites. Although gender, financial situation and nationality were significant health status predictors, they could explain only 8.2 % of the total variance of health status in the multivariable model. A comparably high number of Hungarian students (95.3 % vs. 67.4 % German and 56.7 % Norwegian) reported that they can currently do a lot/very much for their health. In contrast, a significant number of Norwegians (73.0 % vs. 63.7 % Hungarian and 51.5 % German) reported that they currently do a lot/very much for their health (chi2-test, p ≤ 0.001). Financial situation, study site and study year were the strongest predictors for health promotion activities (Nagelkerkes R2 = 0.06). Conclusions Based on our study, gender and study year played only a minor role in the health status and health promotion beliefs and activities of medical students. Structural (study site) and somewhat socio-cultural factors (nationality, financial situation) mainly explained the differences regarding health promoting behaviors. Obligatory, free-of-charge courses for health promotion (activity and relaxation) should be included in study curriculums.